Behavioural responses to science-based eco-labelling: gold, silver, or bronze. Issue 39 (21st August 2018) - Li, Tongzhe; Kecinski, Maik; Messer, Kent D.
ABSTRACT: This study uses unique data collected from field experiments to investigate consumer willingness to pay (WTP) for otherwise homogeneous commodities that provide different levels of environmental services. On average, individuals are willing to pay more for products that provide a higher level of ecosystem services. This effect is larger when the label contains symbols that explicitly differentiate the levels. The effect magnitude is further amplified when it contains brief information on the scientific basis for the levels. However, our results also suggest that the WTP premium for the superior product is smaller than the discount in WTP for the inferior product.